Competence, competition and collaboration: Perceived challenges among Swedish community pharmacists engaging in pharmaceutical services provision and research. (1st February 2019) - Frisk, Pia; Holtendal, Clary; Bastholm-Rahmner, Pia; Sporrong, Sofia Kälvemark
Abstract: Background: Creating evidence of effectiveness is an important part of service development. In an ongoing research project Swedish community pharmacists participate in services research by recruiting patients initiated on statins to an adherence-promoting cognitive pharmaceutical service, jointly run by nurses and pharmacists. Aims: To explore the pharmacists' experiences of providing part of the service and their views regarding future participation in practice research aiming at developing cognitive pharmaceutical services. Methods: Focus group interviews were conducted with community pharmacists from pharmacies participating in the project. A semi-structured interview guide was developed, based on the aim and earlier research. Results: The domains identified were the service itself, operative conditions, the pharmacists' role/profession and stakeholders. The research project was thought to promote the local pharmacy to customers, increase job satisfaction and contribute to service development. However, a perceived lack of competence among pharmacists affected both patient communication and project involvement. Additional resources and strengthened collaboration with other local healthcare were requested. Competition among pharmacy chains was identified as a barrier to patient-centred service provision and research. Conclusion: The current operative conditions in Swedish community pharmacies were perceived by pharmacists as hampering cognitive pharmaceutical services provision and research. Additional resources, improved communication skills and research competence, and increased collaboration with other healthcare and across pharmacy chains are necessary changes. A stronger patient-centred perspective among all stakeholders is required.